The Effect of High Hydrostatic Pressure and Enzymatic Treatment on Microstructural Protein Changes in Hypoallergenic Skim Milk: Literature Study - Syahbanu, Fathma; Kurnianto, Muhammad Alfid (Jurnal Sains dan Teknologi Pangan, 2023)
Food allergy is one of the major health problems worldwide in both adults and children, and its prevalence has been increasing over the last two decades. Epidemiological studies report that Cow's Milk Allergy (CMA) is considered one of the most common food allergies especially in early childhood with an incidence of 2 - 7.5% in population studies in various countries. Many cow's milk allergies occur due to the high intake of milk both in raw and processed form. One of the main allergens in skim cow's milk is beta lactoglobulin. The microstructure approach to modify the structure of milk protein is one of the effective methods in preventing allergies. This manuscript review was conducted using the literature review narrative method. Several food treatments can be effectively used to reduce the allergenicity of milk protein by changing the microstructure of the protein, including enzymatic treatment and High Hydrostatic Pressure. The size reduction caused by both treatments results in allergenic proteins being unable to reach the antibody paratope. The tendency of antigenic milk proteins to become immunological sensitizing agents decreases due to these microstructural changes. The protein microstructure modification can be utilized as a new breakthrough in obtaining hypoallergenic milk-based food products in the future. The purpose of this review article is to discuss the enzymatic and HHP treatment of milk protein microstructure, especially its ability to reduce the number of allergenic proteins in milk.